A Compilation of Moored Current Meter Data, Whitehorse Profiles and Associated Oceanographic Observations. Volume XX. Rise Array, 1974. - Spencer,Ann (1979)
Ocean current and temperature measurements are presented from instruments deployed during 1974 on the continental rise (36 - 40 deg N, 69 - 70 deg W). Current meters were set primarily at depths of 200 and 1000 meters above the bottom, and all the records of 9 months duration. Basic data are displayed as scatter plots, progressive vector diagrams, spectral plots and time series plots; statistical quantities are displayed in tables. Filtered time series are shown in composite displays. Data from a vertical current profiler, the 'whitehorse', are shown as basic profiles or current components and filtered, averaged vector profiles. Selected CTD data included and displayed as plots of potential temperature and salinity versus pressure, and as T-S diagrams. Sponsored in part by Grant NSF-OCE74-01282. See also Volume 19, AD-A070 235.